Analysis and synthesis of multidimensional system classes using linear matrix inequality methods - Paszke, Wojciech (1975- ) (Zielona Góra: Oficyna Uniwersytetu Zielonogórskiego)
The main objective of this dissertation is to convert non-trivial problems in analysis and synthesis of linear repetitive processes (LRPs) and multidimensional (n-D) systems into an linear matrix inequality (LMI) framework for solving them efficiently with recently developed software packages. In particular, the problem is to apply LMI methods for n-D system classes with parameters uncertainty, disturbances and delays occurrence. Resulting LMI conditions are implemented as Matlab m-files.
Keywords: rozprawa doktorska; nauki techniczne; informatyka; metody numeryczne; optymalizacja wypukła; liniowe nierówności macierzowe; układy wielowymiarowe; liniowe procesy powtarzalne